Renal tubular Sirt1 attenuates diabetic albuminuria by epigenetically suppressing Claudin-1 overexpression in podocytes - Hasegawa, Kazuhiro; Wakino, Shu; Simic, Petra; Sakamaki, Yusuke; Minakuchi, Hitoshi; Fujimura, Keiko; Hosoya, Kozi; Komatsu, Motoaki; Kaneko, Yuka; Kanda, Takeshi; Kubota, Eiji; Tokuyama, Hirobumi; et al. (Nature medicine, 2013)
Diabetic nephropathy is the most common cause of end-stage renal disease. Shu Wakino and colleagues now show that high-glucose conditions in the renal proximal tubules result in downregulation of Sirt1 expression there and in the glomeruli, resulting in epigentic upregulation of Claudin-1 in the glomeruli and thus proteinuria. They also show that genetic or chemical targeting of Sirt1 in the kidney is sufficient to improve kidney function in a mouse model of diabetic nephropathy. Sirtuin 1 (Sirt1), a NAD + -regulated deacetylase with numerous known positive effects on cellular and whole-body metabolism, is expressed in the renal cortex and medulla. It is known to have protective effects against age-related disease, including diabetes. Here we investigated the protective role of Sirt1 in diabetic renal damage. We found that Sirt1 in proximal tubules (PTs) was downregulated before albuminuria occurred in streptozotocin-induced or obese ( db / db ) diabetic mice. PT-specific SIRT1 transgenic and Sirt1 knockout mice showed prevention and aggravation of the glomerular changes that occur in diabetes, respectively, and nondiabetic knockout mice exhibited albuminuria, suggesting that Sirt1 in PTs affects glomerular function. Downregulation of Sirt1 and upregulation of the tight junction protein Claudin-1 by SIRT1-mediated epigenetic regulation in podocytes contributed to albuminuria. We did not observe these phenomena in 5/6 nephrectomized mice. We also demonstrated retrograde interplay from PTs to glomeruli using nicotinamide mononucleotide (NMN) from conditioned medium, measurement of the autofluorescence of photoactivatable NMN and injection of fluorescence-labeled NMN. In human subjects with diabetes, the levels of SIRT1 and Claudin-1 were correlated with proteinuria levels. These results suggest that Sirt1 in PTs protects against albuminuria in diabetes by maintaining NMN concentrations around glomeruli, thus influencing podocyte function.